ChemInform Abstract: Review on the Explosive Consolidation Methods to Fabricate Tungsten Based PFMs. Issue 15 (24th March 2016) - Wang, Shuming; Sun, Chongxiao; Guo, Wenhao; Yan, Qingzhi; Zhou, Zhangjian; Zhang, Yingchun; Shen, Weiping; Ge, Changchun
Abstract: Review: PFM: plasma facing material; 20 refs.